DETERMINAN PERMINTAAN KARET INDONESIA - Muhammad Hartana I Putra (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2012)
The aim of this research is to analyze the factors that determinant the rubber demand by Unites States of America. The analysis method of this research is Partial Adjustment Model. Demand of Indonesia rubber by United States of America at research time line of 1995.1 up to 2007.4, simply only influenced by the price of rubber in international market. As for international price influence of rubber to demand of rubber by United States of America from Indonesian is significant and negativity. Whereas other independent variable is federal exchange rate and US’s GDP doesn't have an effect on to demand of rubber by United States of AmericaDOI: 10.15408/sjie.v1i2.2603